CLIMATE-JUST BEHAVIOR foundations and transformational approaches. - Stoll-Kleemann, Susanne; Nicolai, Susanne ([S.l.] : ROUTLEDGE, 2024)
This book highlights the obstacles to and potential for a just transformation as a way out of the current climate crisis. This volume examines the barriers, opportunities and incentives around the pursuit of climate-just behavior, based on a comprehensive interdisciplinary and integrative analysis. It investigates how the gap between expressing concern about the climate crisis and giving it a high priority within the context of everyday behavior can be overcome. At the same time, it looks at the challenging politico-economic framework conditions such as the strong economic growth and profit orientation of capitalism. Although justice is a fundamental human motive, which should induce climate-just behavior, system justification is common and makes people rather justify their unjust behavior. In this book, a general and systemic framework on human behavior is provided, including internal factors, such as knowledge and psychological needs, external factors, such as socio-cultural and politico-economic factors, feedback loops and interactions. The authors draw on multiple theories to examine how denial and moral disengagement affect individual responsibility, despite real-world evidence of the climate crisis. The book highlights the role of emotions in encouraging a pro-environmental response and discusses solutions on both the individual and the collective level, such as transparency laws. Moreover, making climate-friendly options more accessible, affordable and convenient facilitates behavior change more effectively. Overall, this book presents knowledge-based, realistic approaches to surmounting these obstacles in order to achieve a more climate-just world. Climate-Just Behavior will be of great interest to students and scholars of climate change, climate justice, environmental geography and environmental psychology.
Keywords: Climate change mitigation; PSYCHOLOGY / Cognitive Psychology